Evaluation of shear strength parameters using shear box tests for slope failures in Penang / Mohamad Zain Hashim, Damanhuri Jamalludin and Muhammad Hafeez Osman - Hashim, Mohamad Zain; Jamalludin, Damanhuri; Osman, Muhammad Hafeez (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
On 11th December 1993, Highland Tower near Hulu Kelang, Selangor toppled due to slope failure causing 48 residents to be killed. It became the worst nightmare to all Malaysians especially to the residents of the un-failed nearby tower as well as in the engineering lines. Since then, many more slope failures have occurred in Malaysia yearly during the rainy seasons. Hence, slope failure has been ranked as the worst natural disasters in Malaysia. Therefore, the studies on slope failures are becomes more important. Slope failure, also referred to as mass wasting, is the down slope movement of rock debris and soil in response to gravitational stresses. There are many factors affecting slope failures such as weaknesses in the composition or structure of the rock or soil; variation in conditions such as change in rainfall, unorganized drainage or surface stability (removal of vegetation). Among these factors, rainfall, earthquake and human activities are important starter factors that are causing slope failures to occur. This study is to determine the soil shear strength under saturated condition along Teluk Bahang-Balik Pulau road Penang. Saturated shear box tests were conducted to determine the shear strength for soil samples taken from slope failure locations.